2007
DOI: 10.3208/sandf.47.195
|View full text |Cite
|
Sign up to set email alerts
|

Non-Uniform Settlement of Compacted Earth Structures Caused by the Deformation Characteristics of Unsaturated Soil on Wetting

Abstract: The soil W water-coupled analysis for unsaturated soil mechanics with theˆnite element method is used to express the behavior of compacted earth structures exposed to rainfall. The constitutive model, which is proposed by Karube et al. (1996Karube et al. ( , 1997 and modiˆed by Karube and Kawai (2001), is formulated for initial and boundary problems and coded as DACSAR-U (Iizuka et al., 2000). A deepˆll, which consists of compacted, unsaturated soil, was analyzed with DACSAR-U. DiŠerent patterns of rainfall we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Ohno et al (2007) demonstrated the appropriateness of the S e hardening model by simulating experiments for unsaturated soils by Kato (1998). Void ratio, In this simulation, the soil-water retention characteristic curve (WRC) model proposed by Kawai et al (2007) is applied as 14.2.…”
Section: Yield Function Of S E Hardening Modelmentioning
confidence: 96%
“…Ohno et al (2007) demonstrated the appropriateness of the S e hardening model by simulating experiments for unsaturated soils by Kato (1998). Void ratio, In this simulation, the soil-water retention characteristic curve (WRC) model proposed by Kawai et al (2007) is applied as 14.2.…”
Section: Yield Function Of S E Hardening Modelmentioning
confidence: 96%
“…Drying and wetting processes involve unique definitions of A α and B α as A D and B D , and A W and B W , respectively. The hysteresis between primary drying and wetting processes is interpolated using the scheme proposed by Kawai et al In the drying process, the SWCC is defined by applying the maximum degree of saturation SrfD as calculated from Equation . The SWCC for the drying process is therefore expressed as SrSnormalr0SrfDSnormalr0bold=11+exp[]AD+BDln()s/s0. …”
Section: Mathematical Modelmentioning
confidence: 99%
“…Among this rare research, Kawai et al (2007) used the constitutive model by Karube & Kawai (2001) to study the non-uniform settlements induced by rainfall infiltration into a compacted earth fill of variable thickness. The authors highlighted the role played by simultaneous occurrences of elastic swelling and plastic compression during wetting (for shallow and deep soil elements respectively) in causing non-uniform settlements.…”
Section: Introductionmentioning
confidence: 99%